Assessing self-regulated learning abilities of Indonesian students using cognitive diagnostic model - Nusantara, Bayuk; Hadi, Samsul; Retnawati, Heri (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study has two objectives: to find out which cognitive diagnostic model (CDM) is suitable for extracting diagnostic information from non-diagnostic measurement data of Indonesian students’ self-regulated learning abilities; and to find out the attributes of self-regulated learning (SRL) abilities that have not been mastered by Indonesian students. This study used a quantitative research method with a retrofitting approach (post-hoc analysis). There were 3,874 respondents, besides there were 22 items of Q-matrix that measure four attributes of SRL ability. The data were analyzed and empirically validated using the R program with the generalized deterministic input and gate (GDINA) package. The results showed that the GDINA model is the most appropriate model for extracting diagnostic information regarding the SRL abilities of Indonesian students. In addition, most Indonesian students have not been able to master the four SRL ability attributes where the planning attribute (A1) is the most difficult attribute for Indonesian students to master.